A Three-phase AC-Voltage Regulator System - Guoshun Zhou; Tu Ya; Shukun Zhao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Three-phase AC-voltage regulatior systems using silicon controlled rectifier (SCR) have been broadly applied in industrial field.This paper introduces a novel design of three-phase AC-voltage regulation trigger circuitry with SCR and STM32 microcontroller, and presents its application in an energy-saving design of oil extractor control system. This design employs photoelectric isolation technique and the inter-phase of three-phase power supply itself, only three groups of triggering signals are required to control the six thyristors’ conducting angles. The generation of high-precision triggering signals and PID control regulator functions are realized by programming the multiple high-performance timers and the AD interface of a STM32 microprocessor. Experiments and in-field tests have shown the feasibility of the proposed scheme. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.3503